Analysis of the Closed Proportional Implementation Plan in the 2024 Election - Arlen Intani (Indonesian Journal of Advanced Research, 2023)
General elections are very important to maintain people's sovereignty and Indonesian democracy. A good election must pay attention to the system and consider the advantages and disadvantages of the system used and find solutions to any deficiencies of the system used. This is because the system used by Indonesia is a country that uses a proportional election system. The proportional election system has been used in Indonesia since 1955. There are two forms of the proportional system that have been used in Indonesia, namely the closed proportional system and the open proportional system. The system currently used is an open proportional system. However, in 2019 the open proportional system caused many problems to occur. Therefore, in this study, researchers analyzed plans for closed proportional implementation in the 2024 election. This research uses a qualitative method, with a literature study approach. From this study, the researchers concluded that elections in Indonesia in 2024 must be based on the evaluation results of several past elections. Starting from constitutional orders, democracy, election budget, fraud, political costs, and human rights. There are fears that the current system will make people's political intelligence and democracy worse off. An open proportional system must be repaired internally in the recruitment of people's representatives. This can be the answer to the weaknesses of an open operational system.